ANALISIS ASPEK K3 MENGGUNAKAN METODE HAZARD IDENTIFICATION AND RISK ASSESSMENT (HIRA) (STUDI KASUS: PABRIK TAHU TEMPE SUPRIADI SEPINGGAN, KOTA BALIKPAPAN) - Deanova, Ariefa Hanna (Jurnal Teknik Industri (JATRI), 2026)
Occupational Health and Safety (OHS) is an essential aspect in every production process, including small-scale food industries such as the Supriadi Sepinggan Tofu and Tempe Factory in Balikpapan City. This study aims to identify potential hazards, assess risk levels, and provide recommendations for controlling work accidents and occupational diseases using the Hazard Identification and Risk Assessment (HIRA) method. The analysis was complemented with a fishbone diagram to determine root causes and pie charts to visualize risk distribution. The research was conducted through field observations, worker interviews, and measurements of temperature and humidity in the production area. Risk values were calculated by combining severity and likelihood, then classified into low, medium, and high categories. The findings revealed that each stage of tofu and tempe production involved potential physical, chemical, ergonomic, and environmental hazards. The most significant risks were burns from hot water splashes during boiling, cuts from slicing, slips on wet floors, and muscle fatigue caused by non-ergonomic postures. Environmental conditions with temperatures of 27.1°C–31.2°C and humidity of 74%–84% further increased health risks and accelerated raw material spoilage. Based on HIRA analysis, several activities were identified as high-risk and require priority control. Recommended measures include the use of Personal Protective Equipment (PPE), improvement of workplace layout, regular machine maintenance, and safety training for workers. This study contributes to enhancing OHS implementation in small-scale food industries by reducing workplace hazards, preventing occupational diseases, and promoting a stronger safety culture while improving productivity.